Comparing the performance of U.S. domestic and international mutual funds. - Lee, Ivan Wei-Min. (2008)
This study examines and compares the risk-adjusted returns between U.S. based international and domestic equity mutual funds using Jensen Measure from 2002 -2007. The benchmarks for comparison were independent and specific to the funds’ characteristics and investment objectives. The results show that for 2002 through 2007, majority of international funds and domestic funds underperformed their relative benchmarks but the international funds outperformed the domestic benchmark. However, in the case of outperformance, majority of the funds’ positive Jensen Measures were statistically insignificant.